2021
DOI: 10.1002/lary.29905
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Comorbidity Indices in Assessing Head and Neck Surgery Outcomes: A Systematic Review

Abstract: Objective: To evaluate the utility of comorbidity index (CI) scores in predicting outcomes in head and neck surgery (HNS). The CIs evaluated were the Charlson Comorbidity Index (CCI), Elixhauser Comorbidity Index (ECI), Kaplan-Feinstein Index (KFI), American Society of Anesthesiologists Physical Status (ASA-PS), Adult Comorbidity Evaluation-27 (ACE-27), National Cancer Institute Comorbidity Index (NCI-CI), and the Washington University Head and Neck Comorbidity Index (WUHNCI).Methods: We report a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…It is more easily acquired and has a similar predictive value compared with the Charlson comorbidity index. The range of resolution in the ECOG scale is very narrow in head and neck cancer patients 30–32 . Transfusion was also associated with a preoperative Hb level below 12.5 g/d ( p < 0.03).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is more easily acquired and has a similar predictive value compared with the Charlson comorbidity index. The range of resolution in the ECOG scale is very narrow in head and neck cancer patients 30–32 . Transfusion was also associated with a preoperative Hb level below 12.5 g/d ( p < 0.03).…”
Section: Discussionmentioning
confidence: 95%
“…The range of resolution in the ECOG scale is very narrow in head and neck cancer patients. [30][31][32] Transfusion was also associated with a preoperative Hb level below 12.5 g/d (p < 0.03). One approach to avoid preoperative anemia could be to correct iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a recent systematic review of 116 studies, ASA (60.3%) and CCI (33.6%) were the most commonly used comorbidity indices to evaluate outcomes in patients with head and neck surgery. 20 When evaluating studies that utilized the CCI, the authors found that it reliably predicted 1-year mortality. In this study, we noted that elevated CCI was associated with an increased risk of 90-day and 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s global health condition was evaluated according to the ASA score (American Society of Anesthesiologists Physical Status classification system) and according to the ACE-27 score. 19 Both scores are simple to apply even retrospectively: the ASA may be universally applied to surgical patients, while the ACE-27 has been specifically validated for the HN cancer population. 19,20…”
Section: Methodsmentioning
confidence: 99%
“…19 Both scores are simple to apply even retrospectively: the ASA may be universally applied to surgical patients, while the ACE-27 has been specifically validated for the HN cancer population. 19,20…”
Section: Methodsmentioning
confidence: 99%